Gambieroxides, a diverse metabolite class produced by the dinoflagellate genera Gambierdiscus and Fukuyoa - Elizabeth M. Mudge; Emillie M.F. Passfield; D. Tim Harwood; Pearse McCarron; J. Sam Murray (Harmful Algae, 2026)

The benthic genus Prorocentrum (Dinophyceae) in Aotearoa New Zealand and Rangitāhua Kermadec Islands: Genetic diversity, distribution, and diarrhetic shellfish toxin profile - Tomohiro Nishimura; J. Sam Murray; Kirsty F. Smith; Lucy Thompson; Joshua Fitzgerald; Emillie Passfield; Muharrem Balci; D. Tim Harwood; Sarah Challenger; Masao Adachi; Lesley L. Rhodes (Harmful Algae, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

The benthic and epiphytic marine dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands, an updated checklist from 2018 to 2024 - Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; Sarah C. Finch; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2025)
A checklist collating records of New Zealand’s benthic and epiphytic dinoflagellate species was published on‐line in 2018 [Rhodes L, Smith KF. 2019. A checklist of the benthic and epiphytic marine dinoflagellates of New Zealand, including Rangitāhua/Kermadec Islands. N Z J Mar Freshw Res. 53:258–277. doi: 10.1080/00288330.2018.1492425 ]. Over the last six years, seventeen species from nine genera (three newly reported genera) have been documented, including sand‐dwelling species. Isolation and identification of species using traditional microscopic techniques combined with analysis of DNA sequencing data has been supplemented by high‐throughput sequencing techniques (i.e. metabarcoding). Toxin data, based on liquid chromatography mass spectrometry (LC‐MS/MS), and toxicity of isolates are included where applicable. Forty‐two benthic and epiphytic dinoflagellate genera, including genera having benthic life stages, have now been recorded in Aotearoa New Zealand coastal waters including Rangitāhua Kermadec Islands (new record genera in bold): Adenoides , Alexandrium , Amphidinium , Archaeperidinium , Azadinium , Biecheleria , Blastodinium , Bysmatrum , Cachonina , Coolia , Crypthecodinium , Cryptoperidiniopsis , Dinophysis , Durinskia , Ensiculifera , Fukuyoa , Fragilidium , Gambierdiscus , Gonyaulax , Gymnodinium , Gyrodinium , Heterocapsa , Karenia , Karlodinium , Kryptoperidinium , Lepidodinium , Ostreopsis , Pelagodinium , Pentapharsodinium , Pfiesteria , Polarella , Prorocentrum , Protodinium , Protoperidinium , Pseudadenoides , Pseudopfiesteria , Scrippsiella , Symbiodinium , Thecadinium , Togula , Vulcanodinium and Woloszynskia.

High ciguatoxin-producing Gambierdiscus clade (Gonyaulacales, Dinophyceae) as a source of toxins causing ciguatera poisoning - Shauna A. Murray; Arjun Verma; Mona Hoppenrath; D. Tim Harwood; J. Sam Murray; Kirsty F. Smith; Richard Lewis; Sarah C. Finch; Shikder Saiful Islam; Amna Ashfaq; Caroline Dornelles De Azevedo; Christopher J.S. Bolch (Science of The Total Environment, 2025)

Investigation of 44-methylgambierone reactivity with periodate: Structural reassignment, solvent instability and formation of a furanoid analogue - Elizabeth M. Mudge; Alistair L. Wilkins; J. Sam Murray; Frode Rise; Christopher O. Miles (Toxicon, 2024)

Temperate coastal fish shows resilience to extreme low pH in early larval stages - Carla Edworthy; Nicola C. James; Warren M. Potts; Murray I. Duncan; Sam Dupont (Journal of Experimental Marine Biology and Ecology, 2024)

Sub-tropical benthic/epiphytic dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; J. Sam Murray; Emillie M F Passfield; Roberta D'Archino; Wendy Nelson; Tomohiro Nishimura; Lucy Thompson; Tom Trnski (Harmful Algae, 2023)

Exploring the risks and benefits of flexibility in biodiversity offset location in a case study of migratory shorebirds - Nicole Shumway; Megan I. Saunders; Sam Nicol; Richard A. Fuller; Noam Ben‐Moshe; Takuya Iwamura; Sun W. Kim; Nicholas J. Murray; James E. M. Watson; Martine Maron (Conservation Biology, 2023)
Biodiversity offsets aim to counterbalance the residual impacts of development on species and ecosystems. Guidance documents explicitly recommend that biodiversity offset actions be located close to the location of impact because of higher potential for similar ecological conditions, but allowing greater spatial flexibility has been proposed. We examined the circumstances under which offsets distant from the impact location could be more likely to achieve no net loss or provide better ecological outcomes than offsets close to the impact area. We applied a graphical model for migratory shorebirds in the East Asian–Australasian Flyway as a case study to explore the problems that arise when incorporating spatial flexibility into offset planning. Spatially flexible offsets may alleviate impacts more effectively than local offsets; however, the risks involved can be substantial. For our case study, there were inadequate data to make robust conclusions about the effectiveness and equivalence of distant habitat‐based offsets for migratory shorebirds. Decisions around offset placement should be driven by the potential to achieve equivalent ecological outcomes; however, when considering more distant offsets, there is a need to evaluate the likely increased risks alongside the potential benefits. Although spatially flexible offsets have the potential to provide more cost‐effective biodiversity outcomes and more cobenefits, our case study showed the difficulty of demonstrating these benefits in practice and the potential risks that need to be considered to ensure effective offset placement.

Molecular detection and distribution of the genera Amphidoma and Azadinium (Amphidomataceae, Dinophyceae) in the coastal waters of Aotearoa/New Zealand - Muharrem Balci; Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; D. Tim Harwood; A. Lincoln MacKenzie; Tony Bui; Catherine Moisan; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2023)
Molecular‐based approaches for harmful algal bloom species, which can be difficult to identify by light microscopy, are important tools for detecting and predicting the blooms. In this study, 84 samples from Aotearoa/New Zealand coastal waters that contained Azadinium ‐like cells were analysed using an Amphidomataceae real‐time PCR assay. Nineteen samples were positive, and 24 Azadinium ‐like clonal isolates were established from these samples. Subsequently, only five isolates from one sampling point were positive using the real‐time PCR assay. Four of the five isolates were genetically identified as Amphidoma languida and one as Azadinium dalianense . The field samples were analysed retrospectively using the species‐specific real‐time PCR assays; Am. languida was detected from the temperate areas, while Az. poporum and Az. spinosum were detected at one site. Two representative strains of each species were analysed by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS), including Am. languida, which is known as toxic in the previous studies, but neither produced the currently monitored azaspiracids (AZAs). These two newly recorded species for New Zealand are important findings. The results highlight the need for more information on the spatio‐temporal variations of potentially toxic Amphidomataceae species and the risk of AZAs in New Zealand coastal waters.

Limited recovery following a massive seagrass decline in subarctic eastern Canada - Mélanie‐Louise Leblanc; Mary I. O'Connor; Zou Zou A. Kuzyk; Fanny Noisette; Kaleigh E. Davis; Ernie Rabbitskin; Laura‐Lee Sam; Urs Neumeier; Rémi Costanzo; Jens K. Ehn; David Babb; C. Julián Idrobo; et al. (Global Change Biology, 2023)
Over the last few decades, there has been an increasing recognition for seagrasses' contribution to the functioning of nearshore ecosystems and climate change mitigation. Nevertheless, seagrass ecosystems have been deteriorating globally at an accelerating rate during recent decades. In 2017, research into the condition of eelgrass ( Zostera marina ) along the eastern coast of James Bay, Canada, was initiated in response to reports of eelgrass decline by the Cree First Nations of Eeyou Istchee. As part of this research, we compiled and analyzed two decades of eelgrass cover data and three decades of eelgrass monitoring data (biomass and density) to detect changes and assess possible environmental drivers. We detected a major decline in eelgrass condition between 1995 and 1999, which encompassed the entire east coast of James Bay. Surveys conducted in 2019 and 2020 indicated limited changes post‐decline, for example, low eelgrass cover ( 50% cover in eastern James Bay since 1995, representing the largest scale eelgrass decline documented in eastern Canada since the massive die‐off event that occurred in the 1930s along the North Atlantic coast. Using biomass data collected since 1982, but geographically limited to the sector of the coast near the regulated La Grande River, generalized additive modeling revealed eelgrass meadows are affected by local sea surface temperature, early ice breakup, and higher summer freshwater discharge. Our results caution against assuming subarctic seagrass ecosystems have avoided recent global declines or will benefit from ongoing climate warming.

Social Network Analysis of a Chimpanzee (Pan troglodytes) Group in Captivity Following the Integration of a New Adult Member - Sergio Díaz; Lindsay Murray; Sam G. B. Roberts; Paul Rodway (International Journal of Primatology, 2020)
Management of primates in captivity often presents the challenge of introducing new individuals into a group, and research investigating the stability of the social network in the medium term after the introduction can help inform management decisions. We investigated the behavior of a group of chimpanzees ( Pan troglodytes ) housed at Chester Zoo, UK over 12 months (divided into three periods of 4 months) following the introduction of a new adult female. We recorded grooming, proximity, other affiliative behaviors, and agonistic behaviors and used social network analysis to investigate the stability, reciprocity, and structure of the group, to examine the effect of rearing history on grooming network position and the role of sex in agonistic behavior. Both the grooming and agonistic networks correlated across all three periods, while affiliative networks correlated only between periods 2 and 3. Males had significantly higher out-degree centrality in agonistic behaviors than females, indicating that they carried out agonistic behaviors more often than females. There was no significant difference in centrality between hand-reared and mother-reared chimpanzees. Overall, the group structure was stable and cohesive during the first year after the introduction of the new female, suggesting that this change did not destabilize the group. Our findings highlight the utility of social network analysis in the study of primate sociality in captivity, and how it can be used to better understand primate behavior following the integration of new individuals.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Impact of acute handling stress, anaesthesia, and euthanasia on fish plasma biochemistry: implications for veterinary screening and metabolomic sampling - Tim Young; Seumas P. Walker; Andrea C. Alfaro; Lauren M. Fletcher; J. Sam Murray; Ronald Lulijwa; Jane Symonds (Fish Physiology and Biochemistry, 2019)

The dinoflagellate genera Gambierdiscus and Ostreopsis from subtropical Raoul Island and North Meyer Island, Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; Arjun Verma; Sam Murray; D. Tim Harwood; Tom Trnski (New Zealand Journal of Marine and Freshwater Research, 2017)
An expedition to North Meyer Island, Kermadec Islands, in November 2015, resulted in the isolation of two Gambierdiscus species, G. australes and a previously unknown Gambierdiscus species maintained in the Cawthron Institute Culture Collection of Micro‐algae as CAWD242. Identifications were based on morphology and DNA sequence data analysis. Nine isolates of G. australes produced maitotoxin‐1 (MTX‐1) ranging from present (detectable but below the confidence level) to 36.6 pg per cell. One further isolate did not produce MTX‐1, but all G. australes isolates produced putative MTX‐3. Isolate CAWD242 was negative for MTX‐1 but produced MTX‐3. Ostreopsis sp. 3 isolated from samples collected during an earlier expedition in 2013 produced low concentrations of palytoxin (PLTX)‐like compounds (0.013 pg per cell), but an isolate of the same species from samples collected in 2015 was non‐toxic. Other dinoflagellates isolated and identified were Coolia malayensis , Amphidinium carterae and Prorocentrum hoffmannianum .

Biogeographic comparisons of the traits and abundance of an invasive crab throughout its native and invasive ranges - Paul E. Gribben; Sam I’Ons; Nicole E. Phillips; Shane W. Geange; Jeffrey T. Wright; Brad R. Murray (Biological Invasions, 2013)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Plant use at an early Islamic merchant town in the West African Sahel: the archaeobotany of Essouk-Tadmakka (Mali) - Sam Nixon; Mary Anne Murray; Dorian Q. Fuller (Vegetation History and Archaeobotany, 2011)